Quantitative assessment of pericervical dentin in mandibular second primary molars through stress distribution analysis: A finite element study - Selvakumar Haridoss; Mathan Rajan R; Anbarasi K; Vijayaragavan E; Kavitha Swaminathan (Journal of Oral Biology and Craniofacial Research)
Objective: The purpose of this study was to quantify the Pericervical Dentin (PCD) in the mandibular second primary molar and its role in maintaining structural integrity under masticatory loads using Finite Element Analysis (FEA). By identifying the distribution and stress-bearing capacity of PCD, we aim to recommend treatment protocols that maintain PCD to improve fracture resistance in pediatric endodontics. Methods: A 3D model of a mandibular second primary molar was generated from Cone Beam Computed Tomography (CBCT) scans and analyzed using FEA software. Simulated masticatory loads of 353.64 N (maximum), 169.3 N (mean), and 8.05 N (minimum) were applied at angles of 0°, 45°, and 90° to represent vertical, lateral, and maximum masticatory forces. PCD was quantified by measuring stress distribution along buccal, lingual, mesial, and distal surfaces. Results: The analysis revealed that the stress-bearing region in the mandibular second primary molar extends approximately 1–1.5 mm from the Cemento-enamel Junction (CEJ) towards the coronal aspect and 1–1.5 mm from the CEJ towards the radicular aspect, creating a critical 3 mm zone of PCD. The highest stress was consistently found within this PCD zone across on all surfaces of the tooth, highlighting its importance for the tooth’s structural stability. Conclusion: A quantitative analysis of the 3 mm PCD zone (coronal and radicular aspect from the CEJ) emphasizes its critical role in strengthening teeth. Based on these findings, we recommend conservative cavity preparation in pediatric endodontics on preserving PCD to avoid structural weakening and improve long-term clinical outcomes.